2021
DOI: 10.1136/postgradmedj-2020-139566
|View full text |Cite
|
Sign up to set email alerts
|

Guidance for providing effective feedback in clinical supervision in postgraduate medical education: a systematic review

Abstract: The primary aim was to systematically review the empirical evidence relating to models and guidance for providing effective feedback in clinical supervision occurring in postgraduate medical education contexts. A secondary aim was to identify the common and differentiating components of models and guidance for providing effective feedback in this context. A systematic review was conducted. Fifty-one records met the inclusion criteria, including 12 empirical studies. Empirical records meeting inclusion criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 38 publications
2
14
0
1
Order By: Relevance
“…For supervisors, the main goals of progress evaluations was to discuss and give feedback on trainee development and to add structure to the learning process. Weallans, et al have developed a composite model for providing effective feedback in clinical supervision (Weallans et al 2022). In correspondence with this model, supervisors in our study reported that during progress evaluations feedback could be given based on past performance, and trainees could be challenged to seek selfassessment.…”
Section: Utility Of Progress Evaluationsmentioning
confidence: 64%
“…For supervisors, the main goals of progress evaluations was to discuss and give feedback on trainee development and to add structure to the learning process. Weallans, et al have developed a composite model for providing effective feedback in clinical supervision (Weallans et al 2022). In correspondence with this model, supervisors in our study reported that during progress evaluations feedback could be given based on past performance, and trainees could be challenged to seek selfassessment.…”
Section: Utility Of Progress Evaluationsmentioning
confidence: 64%
“…Medical educators are proposing a variety of teaching reforms for medical students at all stages of theoretical teaching, clinical practice, and residency training in order to produce qualified clinical medical personnel for society. [ 15 17 ] Emergency medicine is a very distinctive emerging clinical medicine specialty whose level reflects to a certain extent of the comprehensive medical level of a hospital or even a country. [ 18 ] As an inseparable part of emergency medicine, emergency surgery has become an independent discipline with rapid development.…”
Section: Discussionmentioning
confidence: 99%
“…In medical education, the most common form of supervision is clinical supervision, which consists of oversight of day-to-day clinical performance with regular feedback 13. The benefits of effective clinical supervision in facilitating learning and performance have been widely recognised in both the medical and nursing literature 14–19. Common features of effective supervision in medicine, pharmacy and nursing literature include availability of supervisor, informative feedback, effective communication and a supportive relationship between the supervisor and the supervisee 18–22.…”
Section: Introductionmentioning
confidence: 99%